1999
DOI: 10.1111/j.1540-8159.1999.tb00502.x
|View full text |Cite
|
Sign up to set email alerts
|

Inducibility of Sustained Ventricular Tachycardia in a Closed‐Chest Ovine Model of Myocardial Infarction

Abstract: The two goals of this study were (1) to develop a closed-chest animal model of monomorphic ventricular tachycardia; and (2) to investigate the effect of dual site pacing on inducibility of ventricular tachycardia. In the first part of the study, 10 of 14 sheep underwent successful induction of myocardial infarction by temporary balloon occlusion of the left anterior descending coronary artery. After a follow-up period of 21-43 days, sustained monomorphic ventricular tachycardia could be induced during programm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 20 publications
1
28
0
Order By: Relevance
“…Ovine infarct, unlike canine models, were chosen because they are predictable and histologically similar to human infarction. 24 Temporary arterial occlusions in ovine models reflect current standard practice of primary percutaneous intervention, resulting in more patchy areas of surviving myocardium with an increase in propensity to VT. 5 Continuous cardiac monitoring was not instituted between procedures, limiting detection of nonfatal arrhythmias. Medical therapy such as β-blockers and angiotensin converter enzyme inhibitors, which affect postinfarct mortality, were also not given in this study.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Ovine infarct, unlike canine models, were chosen because they are predictable and histologically similar to human infarction. 24 Temporary arterial occlusions in ovine models reflect current standard practice of primary percutaneous intervention, resulting in more patchy areas of surviving myocardium with an increase in propensity to VT. 5 Continuous cardiac monitoring was not instituted between procedures, limiting detection of nonfatal arrhythmias. Medical therapy such as β-blockers and angiotensin converter enzyme inhibitors, which affect postinfarct mortality, were also not given in this study.…”
Section: Study Limitationsmentioning
confidence: 99%
“…A 0.014-inch coronary angioplasty wire was selectively passed into the homonymous artery (ovine left anterior descending artery equivalent). A 3.0ϫ20 mm coronary angioplasty balloon was deployed midway in the homonymous artery equivalent for 3 hours as described by Reek et al 23 After balloon deflation, each animal was observed on the anesthetic table with full hemodynamic monitoring for 1 hour. After this, all sheaths were removed and the animal recovered and observed for a further 1 to 3 hours, and given analgesia with 0.3 mg IM buprenorphine.…”
Section: Myocardial Infarction Inductionmentioning
confidence: 99%
“…Myocardial infarction was induced in 12 Wether sheep (45Ϯ6 kg) with the percutaneous technique described by Reek et al 15 Briefly, anesthesia was induced with intravenous thiopental (15 mg/kg) after premedication with intramuscular xylazine (0.1 mg/kg). The sheep were intubated, and anesthesia was maintained with isoflurane (1% to 3%) in 100% oxygen.…”
Section: Infarct Inductionmentioning
confidence: 99%